Nano Carbon-based as Supercapacitor Electrode from Cocoa Skin - Pangarso, Zulkaisi Dwi; Cahyaningsih, Lina; Kurnia, Kahfi Imam Faqih; Purwaningsih, Dyah (Proceeding International Conference on Science and Engineering, 2020)
Most cocoa shells contain carbon which can be used as an electrode. Through nano carbon, cocoa skin has the potential to be an electrode material in supercapacitors. Nano carbon is a form of carbon that has a large surface area and pore volume. Material characteristics through FT-IR test showed that the intensity of wave absorption in the graphite group (C-C) decreased which indicates an increase in carbon. The XRD results show that carbon nano has a peak of purity close to graphite at 2?: 24.75º on the lattice values (002). So that the nano carbon based supercapacitor electrode has an electrode resistance value of 0.0307 S/m with a specific capacitance value of 5.19 F/g.